1985
DOI: 10.1136/gut.26.10.1080
|View full text |Cite
|
Sign up to set email alerts
|

Incompletely and completely healed duodenal ulcers' outcome in maintenance treatment: a double blind controlled study.

Abstract: SUMMARY A six month, double blind, controlled study was performed in 107 asymptomatic duodenal ulcer patients who, after short term cimetidine treatment, showed complete or incomplete endoscopic healing. Patients were stratified according to the type of healing and randomly allocated to cimetidine (200 mg at lunch, 400 mg at bedtime) or placebo. Endoscopic examinations were carried out after six months or when symptoms recurred. Eighty seven patients completed the maintenance trial. Of the 56 patients admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…8 In a study investigating differences between S 1 -stage and S 2 -stage scars, using endoscopic ultrasonography (EUS) during H 2 RA administration for GU, an ulcer echo remained and the tissue under the regenerated epithelium had not healed completely in S 1 -stage patients. 17,18 This may cause the recurrences from S 1 -stage to be more frequent than those in patients with the S 2 -stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In a study investigating differences between S 1 -stage and S 2 -stage scars, using endoscopic ultrasonography (EUS) during H 2 RA administration for GU, an ulcer echo remained and the tissue under the regenerated epithelium had not healed completely in S 1 -stage patients. 17,18 This may cause the recurrences from S 1 -stage to be more frequent than those in patients with the S 2 -stage.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, healing should be evaluated by the S 2 -stage scar, because S 1 -stage scars with residual redness have been reported to show a higher recurrence rate than S 2 -stage scars with no redness. 7,8 However, there is a risk of mis-evaluation in the diagnosis of S 1 and S 2 stage scars that are based on the color of the regenerated mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two scar stages, the red scar stage (S1) is the result of either recent ulcer healing or an incompletely healed ulcer, while the white scar stage (S2) describes a completely healed lesion. Patients with incompletely healed ulcers have a higher ulcer crater recurrence rate than those with complete healing 12 . Recurrences are more frequent in cases with a history of previous relapse, 13 , 14 and patients who readily heal on placebo therapy have a more benign form of ulcer disease, less disposed to recurrences, than those treated with antisecretory agents 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with incompletely healed ulcers have a higher ulcer crater recurrence rate than those with complete healing. 12 Recurrences are more frequent in cases with a history of previous relapse, 13,14 and patients who readily heal on placebo therapy have a more benign form of ulcer disease, less disposed to recurrences, than those treated with antisecretory agents. 15 Therefore, the white scar stage of duodenal ulcer in patients with no past history of duodenal ulcer carries with it the smallest probability of ulcer relapse.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that complete healing of a GU by hospital admission improves the prognosis of the patient over the subsequent 4 years [16]. Italian workers have shown that incomplete healing of DU adversely affects prognosis whether maintenance therapy is placebo or cimetidine [67]. Lance and Gazzard found that complete healing of duodenal ulcers did not influence prognosis [68].…”
Section: Role Of Methods Of Initial Healing On Recurrence Ratementioning
confidence: 99%